IbM BANTUAN ALAT DAN PELATIHAN UNTUK PENGEMBANGAN KEAHLIAN WIRAUSAHA PERAKITAN BAHAN GALVALUM UNTUK SANTRI PONDOK PESANTREN DARUL MUTTAQIN BATU - Bintarto, Redi; Sugiarto, Sugiarto; Gayuh Utami Dewi, Francisca; Purnowidodo, Anindito; Dwi Widodo, Teguh; Raharjo, Rudianto (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
Galvalum has become an inevitable part of Darul Muttaqin Batu Islamic Boarding School construction. The ease of access, affordability, and simplicity of installation have led to most buildings within the boarding school using galvalume. However, professional galvalume workers are still employed when it comes to the structure and construction at the boarding school. As a result, the boarding school has to incur high costs to construct or create equipment made from galvalume. In addition to the above-mentioned issues, the students are a valuable human resource that can be utilized to create equipment from galvalume. However, because the students are not yet familiar with how to cut, assemble, and create kit from galvalume materials, training is essential to provide them with additional skills alongside their religious studies at the boarding school. This endeavor involves the contribution of equipment for galvalume material manufacturing and training on assembling galvalume materials according to the boarding school's needs. Through these activities, it is hoped that knowledge will be transferred from the university/instructor to the students. Consequently, this not only equips the boarding school but primarily provides the students with skills so that when they graduate from the boarding school, they have the skills to lead a decent and self-sufficient life.